Plasma cytokine profile on admission related to aetiology in community‐acquired pneumonia. (16th August 2019) - Burgmeijer, Eduard H.; Duijkers, Ruud; Lutter, René; Bonten, Marc J. M.; Schweitzer, Valentijn A.; Boersma, Wim G.
Abstract: Background: Potentially unnecessary antibiotic use for community‐acquired pneumonia (CAP) contributes to selection of antibiotic‐resistant pathogens. Cytokine expression at the time that treatment is started may assist in identifying patients not requiring antibiotics. We determined plasma cytokine patterns in patients retrospectively categorized as strict viral, pneumococcal or combined viral‐bacterial CAP. Objective: To investigate whether cytokine‐based prediction models can be used to differentiate strict viral CAP from other aetiologies at admission. Methods: From 344 hospitalized CAP patients, 104 patients were categorized as viral CAP ( n = 17), pneumococcal CAP ( n = 48) and combined bacterial‐viral CAP ( n = 39). IL‐6, IL‐10, IL‐27, IFN‐γ and C‐reactive protein (CRP) were determined on admission in plasma. Prediction of strict viral aetiology was explored with two multivariate regression models and ROC curves. Results: Viral pneumonia was predicted by logistic regression using multiple cytokine levels (IL‐6, IL‐27 and CRP) with an AUC of 0.911 (95% CI: 0.852‐0.971, P < .001). For the same patients the AUC of CRP was 0.813 (95% CI: 0.728‐0.898, P < .001). Conclusions: This study demonstrated differences in cytokine expression in selected CAP patients between viral and bacterial aetiology. Prospective validation studies are warranted.